Motivating students with learning disabilities to read - Wei, Yan; Spear-Swerling, Louise; Mercurio, Mia (Intervention in School and Clinic, 2021)
Students may lack the motivation to read for many reasons, including inadequate access to interesting texts, limited encouragement to read for pleasure from adults, instructional practices that do not foster engagement in learning, or a history of reading failure. This article focuses on students with reading disabilities who may have a long-standing dislike of reading born of repeated negative experiences with learning to read. Motivating these students to read for pleasure may seem like an unattainable goal. However, past difficulties in reading do not necessarily mean that children will dislike reading forever. In conjunction with appropriate academic interventions, student interest in reading might be improved by motivational interventions aligned with a theoretical framework discussed in this article: (a) choosing interesting texts to read, (b) stimulating knowledge-based interest, and (c) enhancing task-based interest.
Keywords: dept.sed; peer-reviewed

The print exposure of teacher candidates in relation to their achievement and self-ratings of early reading experiences - Spear-Swerling, Louise; Wei, Yan; Dostal, Hannah; Hernandez, Brittney (Reading and Writing, 2020)
This study examined the print exposure of teacher candidates (N = 195) in relation to their GPAs, achievement in reading and writing on the SAT, and their self-ratings of their own early (K to Grade 5) reading experiences. Participants came from undergraduate and Masters programs in varied certification areas and from two different universities. Print exposure measures included author recognition tests for both fiction and nonfiction; a questionnaire about participants’ current voluntary reading habits for books, magazines, newspapers, and digital print media; and favorite authors/books questions. Exploratory factor analysis suggested four factors underlying the different print exposure measures: (1) fiction book reading volume; (2) current magazine and newspaper reading; (3) nonfiction book reading volume and (4) current book reading habits for enjoyment. Only fiction and nonfiction book reading volume related positively to participants’ achievement, in writing as well as reading, and to their early reading experience ratings. A subgroup of participants who had taken a specific reading methods course involving structured language content, and who had positive early reading experience self-ratings, had higher performance in the course than did participants with mixed or negative self-ratings, although the two groups did not differ in overall GPA. Findings support the view that different measures of print exposure tap somewhat different aspects of print exposure, with differing relationships to varied indicators of achievement. Results also support concerns about the reading volume and print exposure of some teacher candidates. © 2020, Springer Nature B.V.
Keywords: Print exposure; Reading; Reading habits; Teacher candidates; Teacher preparation; Writing; dept.sed; peer-reviewed

Culturally Responsive Special Education - Gerzel-Short, Lydia; Jerae, Kelly; Hovey, Katrina A.; Hsiao, Yun‐Ju; Wei, Yan (Advances in educational marketing, administration, and leadership book series, 2023)
Keywords: dept.sed

Preparing culturally responsive teachers: a systematic review - Miller, Rhonda D.; Gerzel-Short, Lydia; Kelly, Jerae H.; Uphold, Nicole; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan (Multicultural Learning and Teaching, 2023)
As the world continues to ponder issues of equity and diversity, U.S. public schools face an expanding demographic divide between teachers and students. While diverse groups of public school students show an increase in population, the teaching workforce in the U.S. remains overwhelmingly White. The purpose of this systematic review is to examine how preservice teachers (PST) are being prepared to be culturally responsive. A total of 26 studies published between 2006 and 2020 were reviewed. The results indicate that PSTs’ learning experiences are varied and tend to be stand-alone approaches focused on changing the attitudes and beliefs of PSTs. Findings also bring to light the vagueness of terminology used in the research to define cultural groups of students, the conspicuous absence of studies related to LGBTQ+ populations, and the lack of study replications. Implications for future research are discussed.
Keywords: culturally responsive; dept.sed; diversity; peer-reviewed; pre-service teacher; teacher education; teacher preparation